Perbedaan Implementasi Belajar Kitab Kuning Antara Santri Salaf dengan Santri Modern di Pondok Pesantren Asasul Ulum - Rahmawati, Adinda Puji; Hanifa, Izza (Dinasti Research, 2025)
This study aims to identify and analyze the differences in the implementation of learning between traditional (salaf) and modern santri at Pondok Pesantren Asasul Ulum. Employing a qualitative case study approach, data were gathered through in-depth interviews and participatory observations of both students and educators. The findings reveal that the implementation of additional review hours for nahwu significantly enhances students' understanding, fostering a collaborative learning environment that bridges traditional and modern educational approaches. This study emphasizes the importance of adaptive teaching methods in pesantren education and highlights how different pedagogical strategies can influence learning outcomes among diverse student groups. The results indicate a clear improvement in students' confidence and their ability to engage with complex materials, reinforcing the necessity for inclusive educational practices in Islamic boarding schools